Unveiling the Burden of Prevalence of Congenital Heart Defects in Down Syndrome Patients in Indonesia: A Systematic Review and Meta-analysis - Pasya Putra Pratama Ali Saini; Lowry Yunita; Sekar Andrea Fernandez (The Indonesian Heart Association, 2026)
Down syndrome or trisomy 21 is frequently accompanied by Congenital Heart Disease (CHD), which is a major cause of mortality and morbidity within the first two years of life in children with Down Syndrome (DS). This systematic review and meta-analysis aimed to analyze the literature to assess the pooled prevalence of overall CHDs among children with DS in Indonesia. The search was conducted across major databases, including PubMed, Google Scholar, ScienceDirect, Cochrane, and Garuda (an Indonesian database), using Boolean operators and a range of keywords. Citation management was performed using the Rayyan Intelligent Systematic Reviews website (https://www.rayyan.ai/). Quantitative data synthesis was conducted using Comprehensive Meta-Analysis version 4.0 (Biostat, Englewood, NJ, USA). Initially, 1,915 citations were retrieved from the primary search; after screening titles and assessing full texts, a total of 11 articles were included in this study. A total of 1,122 subjects from 11 different studies were analyzed. The overall pooled prevalence of CHDs among children with DS was 44.6% (95% CI: 34.9% to 54.8%). We also found a high degree of heterogeneity between the studies (I² = 88.8%), and inspection of the forest plot revealed that the distribution of the plotted data was asymmetrical. Approximately one in two children with DS in Indonesia has at least one type of CHD. These findings highlight the need for early routine cardiac screening to reduce morbidity and mortality. We recommend further research to provide more data to assess the prevalence of CHD